ANALISA PENGARUH MOTIVASI KARYAWAN DAN STRATEGI PEMASARAN MUSEUM TERHADAP PENINGKATAN JUMLAH PENGUNJUNG DI MUSEUM PURNA BHAKTI PERTIWI JAKARTA - Sri Yanthy Yosepha (JURNAL MITRA MANAJEMEN, 2015)
ABSTRACTThe goal of the research was analyzed the influence of motivation of employees, and marketing strategies to increase the amount of visitor of Purna Bhakti Pertiwi museum wheresamples were taken from 100 respondents from amount of population counted 20502 people,those were taken from amount of employees and visitors of Purna Bhakti Pertiwi Museum whowere selected randomly.This research used to descriptive analyze, the result of this research showed that (1) therewas little influence motivation of employee to increase the amount of visitors of Museum andbe accepted (2) there was strong and positive influence of marketing strategies toward toincrease of amount of visitors of Purna Bhakti Pertiwi of Museum. (3) There was the positiveand strong influence of motivation of employee, and marketing strategies toward to increasethe amount of Purna Bhakti Pertiwi of Museum.Key word : Motivation of employees, Marketing strategies, Visitor of Museum.